Evolution of Myocardial Hypertrophy Associated With Pregnancy in Hypertensive Women Six Months Postpartum - Vasconcelos, Milena Miranda [UNESP]; Ganan, Camilla Sousa [UNESP]; da Silveira, Caroline Ferreira da Silva Mazeto Pupo [UNESP]; Malagutte, Karina Nogueira Dias Secco [UNESP]; Poiati, Juliane Rosa [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP]; Martin, Luis Cuadrado [UNESP]; Bazan, Rodrigo [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Bazan, Silméia Garcia Zanati [UNESP] (Elsevier, 2023)
Systemic arterial hypertension (SAH) is one of the principal risk factors for developing cardiovascular disease. When a hypertensive woman becomes pregnant, new hemodynamic condition is installed, with addition from chronic pressure overload to chronic volume overload. This new hemodynamic condition can provide greater myocardial hypertrophy(LVH), whose postpartum evolution has been little studied in the literature. To evaluate LVH in hypertensive women in the third trimester of pregnancy and 6 months postpartum and to establish which clinical variables are associated with elevated risk of LVH. Prospective longitudinal study including 41 pregnant women beyond 35 gestational weeks and with previous SAH. They were submitted to clinical and echocardiographic evaluation at the gestational period and 6 months postpartum. Statistical analysis: multivariate logistic regression with the exposures most strongly associated with maintenance of hypertrophy in univariate analysis. Significance level: P<0.05. The mean age was 29±6.2 years. The majority of the women were white(85.4%). Before pregnancy 23(59%) women used antihypertensive drugs and 28(71.8%) used during pregnancy. At the end of gestation, all women presented LVH, 79% maintained hypertrophy 6 months postpartum. In multivariate analysis, exposures significantly associated with hypertrophy maintenance: systolic blood pressure(SBP) at the end of gestation, OR=1.16(1.03-1.30);P=0.013 and SBP increase at 6 months postpartum in relation to end of gestation, OR=22.9(1.8-294);P=0.016. In hypertensive pregnant women, LVH frequency is elevated at the end of pregnancy, and recovery frequency of this hypertrophy, at 6 months postpartum, is very low. The increase of SBP 6 months postpartum was associated with maintenance of hypertrophy.